Boundary output feedback control of a flexible spacecraft system with input constraint. Issue 5 (18th January 2018) - Fu, Yun; Liu, Yu; Huang, Daoping
Abstract : This study is concerned with vibration control of a flexible spacecraft system in the presence of disturbances and input saturation constraint. The dynamics of the spacecraft consisting of a rigid body and two flexible appendages is presented by the coupled partial differential equations and ordinary differential equations. The first boundary state feedback control is adopted when the spacecraft system states can be measured. The second boundary output feedback control is employed when there exists the unmeasurable state in the proposed control law. A high‐gain observer is developed to estimate the unmeasurable system state, two auxiliary systems are designed to prevent the presence of input saturation from destroying the system performance and two disturbance observers are established to handle the unknown boundary disturbances. The well‐posedness and stability of the spacecraft system are proved. Simulation results are presented to demonstrate the effectiveness of the proposed control schemes.